Preparing ultra-stable Ru nanocatalysts supported on partially graphitized biochar via carbothermal reduction for hydrogen storage of N-ethylcarbazole. (21st July 2021) - Qin, Yibo; Shi, Jiaming; Bai, Xuefeng
Abstract: A highly active and ultra-stable partially graphitized bio-carbon (pg-BC) supported Ru nanoparticles (RuNPs/pg-BC) catalyst was prepared by wet impregnation-carbothermal reduction method. The structure, morphology and surface characteristics of the prepared Ru/pg-BC catalysts were characterized by N2 physical adsorption, XRD, XPS, TEM and Raman. The results indicate that the spherical Ru nanoparticles with an average particle size of 2.97 nm are uniformly dispersed on the carbon support, and BC is partially graphitized under the effect of Ru 3+ at a lower temperature, graphitization enhancing the catalytic activity of RuNPs/pg-BC. The conversion of N-ethylcarbazole (NEC) and the selectivity of 12H-NEC were 100% and 99.41% for 70 min at 130 °C and 6 MPa H2, respectively. RuNPs are embedded in the cavities formed by carbothermal reduction on the surface of pg-BC, which can improve the catalytic stability of RuNPs/pg-BC. After the catalyst was recycled 9 times, the catalytic performance did not significantly decrease, showing ultra-high stability. Graphical abstract: Image 1 Highlights: Biochar can be used as carrier and reducing agent during carbothemal reduction. Ru 3+ can promote the partial graphitization of biochar at the lower temperature. The graphitization of biochar (pg-BC) enhances the catalytic activity of Ru/pg-BC. RuNPs are embedded in the caves on the BC surface to improve catalytic stability.